Recent advances in microbial engineering approaches for wastewater treatment: a review - Sharma M.; Agarwal S.; Agarwal Malik R.; Kumar G.; Pal D.B.; Mandal M.; Sarkar A.; Bantun F.; Haque S.; Singh P.; Srivastava N.; Gupta V.K. (My University, 2025)
In the present era of global climate change, the scarcity of potable water is increasing both due to natural and anthropogenic causes. Water is the elixir of life, and its usage has risen significantly due to escalating economic activities, widespread urbanization, and industrialization. The increasing water scarcity and rising contamination have compelled, scientists and researchers, to adopt feasible and sustainable wastewater treatment methods in meeting the growing demand for freshwater. Presently, various waste treatment technologies are adopted across the globe, such as physical, chemical, and biological treatment processes. There is a need to replace these technologies with sustainable and green technology that encourages the use of microorganisms since they have proven to be more effective in water treatment processes. The present review article is focused on demonstrating how effectively various microbes can be used in wastewater treatment to achieve environmental sustainability and economic feasibility. The microbial consortium used for water treatment offers many advantages over pure culture. There is an urgent need to develop hybrid treatment technology for the effective remediation of various organic and inorganic pollutants from wastewater.; Microbial engineering approaches for wastewater treatment.Current and emerging sources of water pollution are discussed.Various treatment technologies for wastewater treatment.Biological methods and microbes are used for degradation.Parameters responsible for the degradations processes of wastewater.